Pengabdian Kepada Masyarakat Melalui Program Kemah Dakwah dan Bakti Mahasiswa (KDBM) di Pondok Pesantren Daarus Sholah - Siti Munfiatik; Ramdanil Mubarok; Reshar Saputra; Annisa Oktaviani (MAYARA: Jurnal Pengabdian Masyarakat, 2023)
Community service through the Da'wah Camp and Student Service (KDBM) program is one form of the Tri Dharma of Higher Education. The purpose of this service is to carry out the service activity items in the da'wah camp program and student service at STAI Sangatta Kutai Timur. The method used in this service is participatory action research (PAR). The results of the dedication show that the da'wah camp program and student service at the Daarus Sholah Islamic Boarding School are carried out with several activity items, namely: congregational prayer assistance and brief advice giving students an understanding of the importance of regularly praying, tidying up and tidying up rows, and knowing the virtues of congregational prayer, Teaching the Koran to students provides understanding to students on how to read the Qur'an properly and correctly and in accordance with the rules of tajwid and makhorijul letters, as well as community service at the service location, resulting in togetherness in protecting the environment and social life. The Daarus Sholah Islamic Boarding School environment has become cleaner, neater, more beautiful, and, of course, healthier. The hope is that with community service through the missionary camp and student service programs, higher education institutions can make a real contribution to the wider community.